Outcome of management of gastroschisis: comparison of improvised surgical silo and extended right hemicolectomy - Philemon E. Okoro; Charles Ngaikedi (SpringerOpen, 2020)
Abstract Background Gastroschisis is onea of the major abdominal wall defects encountered commonly in pediatric surgery. Whereas complete reduction and abdominal closure is achieved easily sometimes, a daunting situation arises when the eviscerated bowel loops and other viscera cannot be returned immediately into the abdominal cavity. This situation is a major contributor to the outcome of the treatment of gastroschisis in our region. In our efforts to improve our outcome, we have adopted the technique of extended right hemicolectomy for cases where complete reduction and primary abdominal wall closure is otherwise not possible. This study compared the management outcome of gastroschisis using our improvised silo, and performing an extended right hemicolectomy. Results Thirty-nine cases were analyzed. Simple closure could not be achieved in 28 cases. In the absence of standard silos, improvised ones were constructed from the amniotic membrane (3 cases), urine bag (4 cases), and latex gloves (9 cases) giving a total of 16 cases managed with silos. Extended right hemicolectomy was performed in 12 cases. Conclusions Given the peculiarities of circumstances in our region regarding human and material resources in the care of gastroschisis patients, an extended right hemicolectomy, to make it possible to close the abdomen primarily in gastroschisis is a more viable option than the use of improvised silo. Trial registration This trial was approved by the Ethical Committee of the University of Port Harcourt Teaching Hospital, Nigeria. Reference Number: UPTH/ADM/90/S.II/VOL XI/835. Registered 3 May 2013.